Integer Programming and Combinatorial Optimization 11th International IPCO Conference, Berlin, Germany, June 8-10, 2005, Proceedings - Jünger, Michael.; Jünger, Michael.; Kaibel, Volker.; Kaibel, Volker. (Theoretical Computer Science and General Issues, 2005)
Since its start in 1990, the IPCO conference series (held under the auspices of theMathematicalProgrammingSociety)hasbecomeanimportantforumforthe presentation of recent results in Integer Programming and Combinatorial Op- mization. This volume compiles the papers presented at IPCO XI, the eleventh conference in this series, held June 8–10, 2005, at the Technische Universit¨ at Berlin. The high interest in this conference series is evident in the large number of submissions. For IPCO XI, 119 extended abstracts of up to 10 pages were submitted. During its meeting on January 29–30, 2005, the Program Committee carefully selected 34 contributions for presentation in non-parallel sessions at the conference. The ?nal choices were not easy at all, since, due to the limited number of time slots, many very good papers could not be accepted. During the selection process the contributions were refereed according to the standards of refereed conferences. As a result of this procedure, you have in your hands a volume that contains papers describing high-quality research e?orts. The page limit for contributions to this proceedings volume was set to 15. You may ?nd full versions of the papers in scienti?c journals in the near future. We thank all the authors who submitted papers. Furthermore, the Program Committee is indebted to the many reviewers who, with their speci?c expertise, helped a lot in making the decisions.